Parkinson's Disease Modeling Using Directly Converted 3D Induced Dopaminergic Neuron Organoids and Assembloids - Hongwon Kim; Soi Kang; Byounggook Cho; Saemin An; Yunkyung Kim; Jongpil Kim (Advanced Science)
Abstract Parkinson's disease (PD) is characterized by the progressive loss of dopaminergic neurons and the accumulation of α‐synuclein aggregates, yet current models inadequately mimic the complex human brain environment. Recent advances in brain organoid models offer a more physiologically relevant platform for studying PD, however, iPSC‐derived brain organoids require long maturation times and may not accurately represent the aged brain's epigenetics and cellular contexts, limiting their applicability for modeling late‐onset diseases like PD. In this study, a novel approach for generating 3D‐induced dopaminergic (iDA) neuron organoids directly from human fibroblasts is presented. It is confirmed that these 3D iDA organoids more closely resemble the aged human brain and accurately replicate PD pathologies. Furthermore, this model is extended by incorporating astrocytes to create 3D iDA neuron‐astrocyte assembloids, recognizing the critical role of glial cells in neurodegenerative processes. It is identified that PD assembloids incorporating control astrocytes with A53T mutant iDAs demonstrated the neuroprotective effects of healthy astrocytes. In contrast, A53T mutant astrocytes progressively contributed to neuronal degeneration and synucleinopathy in 3D‐iDA assembloids. These findings suggest that directly converted 3D‐iDA organoids and assembloids provide a robust and physiologically relevant model for studying PD pathogenesis and evaluating therapeutic interventions.